“Offi cial Section” Smolensk Diocesan Gazette as a Source on the History of Smolensk (1865–1918) - Hieromonk Rafail (Ivochkin D.) (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article reveals the main directions of the publications in the «Oﬃ cial Section» «Smolensk Diocesan Gazette». The study looks at the diocesan statement as a historical source on diﬀerent aspects of the life of the Smolensk diocese in the second half of 19th — early 20th centuries. Studied such directions of the department, as the current life of the diocese in the period under review, the issues of social and cultural activities and enlightenment Smolensk clergy. Much attention is paid to the analysis of publications about hramostroitelstva, pastoral care of schools of spiritual department, genealogy clergy. While working on the article used an integrated approach, general scientiﬁ c dialectical method of study and analysis of social phenomena, including the principles of objectivity, historicism and systematic. The results will enable objectively present not only the history of the Smolensk diocese, but the Russian Orthodox Church.